Oliver Twist - Lean, David, 1908-1991.; Alec, Guinness; Francis L Sullivan; Henry Stephenson; John Howard Davies; Kay Walsh; Mary Clare; Robert Newton (UK Independent Producers, 1948)
Based on the Charles Dickens novel Oliver Twist is about an orphan boy who runs away from a workhouse and meets a pickpocket on the streets of London. Oliver is taken in by the pickpocket and he joins a household of young boys who are trained to steal for their master. The boys thieving activities and others who desire to cash in on Oliver's fortune by criminals activities leads to murder and community outrage as they are hunted down. This version of Oliver Twist is topped by Alec Guinness's masterly performance of arch-thug Fagin.
Based on the Charles Dickens novel Oliver Twist is about an orphan boy who runs away from a workhouse and meets a pickpocket on the streets of London...
Charles Dickens
Languages: English, Turkish Subtitles: English, Turkish, French
Keywords: Crime; Drama; Adventure